THE UTILIZATION OF INSTAGRAM AS MODERATING VARIABLE BETWEEN GEOGRAPHY LEARNING OUTCOMES AND DISASTER PREPAREDNESS - Afrian, Ramdan; Urfan, Faiz; Islami, Zukya Rona (Universitas Pendidikan Indonesia, 2020)
This study aims to analyze the use of Instagram as a moderating variable between Geography learning outcomes and disaster preparedness in high school level students. The study conducted in Langsa City, Aceh Province, with a sample of research from public high schoolâ€™s students in Langsa City. The sample selection technique is random purposive sampling. The Data analyzed by linear regression test with moderating variables using IBM SPSS 22. The results showed that the use of Instagram did not increase the impact of learning outcomes on disaster preparedness. This is evidenced by the significance value of the variable use of Instagram by 0.231 which is greater than 0.05. However, Geography learning outcomes variable has a large influence on disaster preparedness (p value = 0.00 and adjusted R2 = 0.660 = 66%).Â The recommendation of this study is the utilization of Instagram needs to be studied in order to help students learn more optimally in Geography subject.